The Influence of Work Motivation on Employee Performance with Organizational Support as an Intervening Variable in BPJS Ketenagakerjaan in the Northern Sumatra Region - Amalia, Ira; Farida Ferine, Kiki (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The purpose of this research is to find out the influence of work motivation on employee performance with organizational support as an intervening variable. Associative quantitative research type. The population is 98 employees, and the sample uses a saturated sample because it counts the entire population as a sample. Data collection is carried out by distributing questionnaires and primary data is the source. The research model used is path analysis and the measuring tool is sem PLS 3.3. The results of the research show that organizational support has a positive and significant effect on employee performance. Work Motivation has a positive and significant effect on Organizational Support. Work Motivation has a positive and significant effect on Employee Performance. Work Motivation has a positive and significant effect on Employee Performance through Organizational Support.